Attitude Formation of Students According to Hadratus Shaykh K.H. Hasyim Asy’ari: An Examination of the Book of Adabul Alim Wa Muta’alim - Erizka Nurianti; Imam Sopingi; Athi’ Hidayati; Hanin Yumna (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Attitude building is an essential aspect in the formation of a student’s personality, especially in the context of Islamic education. KH. Hasyim Asy’ari, through the book Adabul Alim Wa Muta’alim emphasizes the importance of fostering students’ manners and attitudes as the main foundation in the learning process. This study aims to explore KH. Hasyim Asy’ari’s thoughts on the ideal attitude of students towards knowledge, teachers, and the learning environment and its relevance to the formation of attitude today. The method used is library research with a qualitative approach. The results of the study show that values such as sincerity, respect, seriousness, and discipline are the main pillars in the formation of student attitude. This idea is very relevant to be applied in the modern education system in order to create a generation that is not only intellectually intelligent, but also noble. This study contributes to the enrichment of Islamic educational discourse by offering a contemporary interpretation of K.H. Hasyim Asy’ari’s classical adab principles, providing educators and policymakers with practical insights to strengthen moral and spiritual character formation in today’s learning environments.